Keselarasan Dalam Teori Koneksionisme dan Prinsip Belajar Islam Serta Implementasinya Pada Remaja - Nurliasari, Hanifa; Gumiandari, Septi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Adolescents have a strong connection with learning activities where in the learning process itself, there are principles or learning theories both in the Islamic and Western spheres. This study aims to examine the allignment between connectionism learning theory and the principles of learning in Islam and the implementation of the relationship between the two in the learning process of adolescents. This research is a library research that is analyzed using content analysis techniques. The results of this study are (1) discussion of connectionism learning theory learning and its three primary laws, (2) learning principles in Islam (3) the alignment between connectionism learning theory and Islamic learning principles, and (4) the implementation of the alignment between connectionism learning theory and learning principles in Islam in adolescents.